Analysis and design of Hutanku application using Rapid application development - Yerik Afrianto Singgalen (Institute of Computer Science (IOCS), 2024)
This research aims to design the Hutanku application for bird location, tree, employee, and visitor databases using Rapid Application Development (RAD). The findings of this study indicate that the databases can be effectively utilized and prove beneficial in monitoring conservation areas. The primary objective of the research is to leverage RAD methodologies to design an application that facilitates efficient data collection, storage, and retrieval for bird locations, tree information, employee records, and visitor data within conservation zones. RAD's iterative and collaborative nature allows for swift adaptation to evolving user requirements, ensuring that the application is well-aligned with the specific needs of conservation monitoring. The successful implementation of the designed application highlights the practical utility of databases in enhancing the monitoring and management of conservation areas. In conclusion, the research underscores the significance of employing RAD for designing the Hutanku application, emphasizing its role in creating a robust database system essential for effective conservation practices